2020
DOI: 10.1186/s12884-020-03037-0
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal genitourinary infections and poor nutritional status increase risk of preterm birth in Gasabo District, Rwanda: a prospective, longitudinal, cohort study

Abstract: Background: Preterm birth (PTB) is a leading cause of early childhood mortality and morbidity, including long-term physical and mental impairment. The risk factors for PTB are complex and include maternal nutritional status and infections. This study aimed to identify potentially modifiable risk factors for targeted interventions to reduce the occurrence of PTB in Rwanda. Methods: We conducted a prospective, longitudinal cohort study of healthy pregnant women aged 18 to 49 years. Women at 9-15 gestational week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…In Rwanda, anemia and low hemoglobin levels are present in 19% women of childbearing age, of which 7% are underweight [13,14]. In a recent study, during early pregnancy, anemia was found to be present in 33% participants; in addition, participants showed deficiencies in iron levels as measured by ferritin and soluble transferrin receptors (sTfRs) (19.1%) [15]. In the same study, 27.3% and 7.9% participants showed high levels of inflammatory markers; C reactive protein (CRP) and alpha A glycoprotein (AGP) suggestive of infection or other inflammatory processes [15].…”
Section: Nutrition and Infection In Pregnancymentioning
confidence: 99%
See 3 more Smart Citations
“…In Rwanda, anemia and low hemoglobin levels are present in 19% women of childbearing age, of which 7% are underweight [13,14]. In a recent study, during early pregnancy, anemia was found to be present in 33% participants; in addition, participants showed deficiencies in iron levels as measured by ferritin and soluble transferrin receptors (sTfRs) (19.1%) [15]. In the same study, 27.3% and 7.9% participants showed high levels of inflammatory markers; C reactive protein (CRP) and alpha A glycoprotein (AGP) suggestive of infection or other inflammatory processes [15].…”
Section: Nutrition and Infection In Pregnancymentioning
confidence: 99%
“…We assessed leukocyte telomere length in healthy pregnant women aged 18-45 years as part of a prospective, cohort study of pregnant women from 10 health centers in Gasabo District, Kigali Province [15]. Participants were enrolled from September to October 2017 as previously described [15] and were in early pregnancy (gestational age 9-15 weeks, as confirmed by ultrasound and self-reported last menstrual period). Inclusion criteria included testing negative for HIV and syphilis, singleton pregnancy, speaking Kinrywanda or English and providing written consent for participation.…”
Section: Participants and Inclusion Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, the effect of maternal urinary tract infection was investigated. Maternal urinary tract infection was found to be associated with prematurity ( 12 ). Howley et al examined the effect of maternal urinary tract infection on birth defects ( 13 ).…”
Section: Introductionmentioning
confidence: 99%